Association Between Functional Impairment, Depression, and Extrapyramidal Signs in Neuroleptic-Free Patients With Alzheimer Disease. (September 2013) - Choi, Junbae; Myung, Woojae; Chung, Jae Won; Kang, Hyo Shin; Na, Duk L.; Kim, Seong Yoon; Lee, Jae-Hong; Han, Seol-Heui; Choi, Seong Hye; Kim, SangYun; Kim, Seonwoo; Carroll, Bernard J.; et al.
Background: Extrapyramidal signs (EPSs) are commonly observed in patients with Alzheimer disease (AD). We report here the base rate of EPS in a large cohort of patients with AD who were not receiving neuroleptic drugs, and the associations of EPS with functional outcomes and depressive symptoms. Methods: In a consortium involving 56 clinics, we recruited 2614 patients with AD. We estimated basic activities of daily living (ADL) and instrumental ADL by the Barthel index and the Seoul-Instrumental Activities of Daily Living (S-IADL) scales, respectively. Depressive symptoms were assessed using the 15-item Geriatric Depression Scale (GDS-15). The EPS group was defined by the presence of at least 1 EPS based on a focused neurologic examination. Results: The prevalence of EPS-positive patients was 12%. These had lower Korean version of the Mini-Mental State Examination (K-MMSE) scores than the EPS-negative cases ( P < .001). After controlling for demographic, medical, radiological, genetic, and cognitive (K-MMSE) factors, the proportion of patients with impaired ADL was significantly higher in the EPS group than in the non-EPS group ( P < .001, odds ratio = 1.90, 95% confidence interval, 1.45–2.48, and logistic regression). The S-IADL scores were significantly higher in the EPS group than this in the non-EPS group ( P < .001, regression coefficient = 3.19, and median regression). The GDS-15 scores were higher in the EPS group ( P = .04, regression coefficient = 0.89, and median regression). Conclusion: The presence of EPS in patients with AD who were not receiving neuroleptic drugs was associated with more impaired basic and instrumental ADL functioning and with greater depression symptoms.